Analysis Of Post COVID-19 Microfinance AT BANK SYARIAH INDONESIA Kcp Bogor Pajajaran Bantarjati - Marlina, Asti; Husna, Siti Asifatul; Hanifan, M. Zakie (Universitas Ibn Khladun Bogor, 2023)
The real estate sector's economic resilience, which is essential for the recovery of the economy following the COVID-19 epidemic, is significantly influenced by financing. However, COVID-19's effects mean that financing cannot operate as previously agreed upon within the allotted time, which causes many debtors to go into default and produce bad debts or non-performing financing. Errors in the application of financing procedures might also result in non-performing financing. Problem funding is attempted to be saved by enforcing bank policies that currently exist. The goal of this discussion is to determine how the bank BSI Bank KCP Bogor Pajajaran Bantarjati's procedures, comparative financing conditions during and after COVID-19, and the resolution of problematic financing have shown a positive trend because it has been successful in lowering the number of customers who restructured from 30% to 0%, non-performing financing from 14% to 7%, and current financing from 56% to 93% during post-COVID-19. The number of customers whose financial situations improved and they were able to pay off their loans also contributed to the upward trend. This demonstrates the efficacy of the financing guidelines and practices put in place by Bank BSI KCP Bogor Pajajaran Bantarjati in an effort to keep the bank in good standing following COVID-19.